Management of congenital ichthyoses: European guidelines of care, part two. (1st March 2019) - Mazereeuw‐Hautier, J.; Hernández‐Martín, A.; O'Toole, E.A.; Bygum, A.; Amaro, C.; Aldwin, M.; Audouze, A.; Bodemer, C.; Bourrat, E.; Diociaiuti, A.; Dolenc‐Voljč, M.; Dreyfus, I.; et al.
Summary: These guidelines for the management of congenital ichthyoses have been developed by a multidisciplinary group of European experts following a systematic review of the current literature, an expert conference held in Toulouse in 2016, and a consensus on the discussions. These guidelines summarize evidence and expert‐based recommendations and intend to help clinicians with the management of these rare and often complex diseases. These guidelines comprise two sections. This is part two, covering the management of complications and the particularities of some forms of congenital ichthyosis.